Contribution of Platelets to Increased Plasminogen Activator Inhibitor Type 1 in Severe Preeclampsia - Gilabert, Juan; Estellés, Amparo; Aznar, Justo; España, Francisco; Andrés, Cristina; Santos, Teresa; Vallés, Juana (Thrombosis and Haemostasis, 1990)
Plasminogen activator inhibitor activity and antigen were evaluated in plasma, serum and platelet lysate in patients with severe preeclampsia (n = 12), and in normal pregnant women (n = 21). Other parameters, including β-thromboglobulin and platelet count, were also evaluated. A significant increase (p <0.05) in β-thromboglobulin was observed in platelet poor plasma of preeclamptic women when compared with that of normal pregnant women, and the platelet count was lower in the preeclamptic group than in the normal pregnant group. A significant increase in plasminogen activator inhibitor activity and antigen was observed in platelet poor plasma of the preeclamptic group as compared with normal pregnant women, whereas platelet lysate from preeclamptic women showed a significant decrease in both plasminogen activator inhibitor activity and antigen as compared with that of normal pregnant women. No correlation between β-thromboglobulin and plasminogen activator inhibitor type 1 antigen in platelet poor plasma was observed, but a significant inverse correlation (r = −0.78, p <0.05) between β-thromboglobulin in platelet poor plasma and plasminogen activator inhibitor-1 antigen in platelet lysate was obtained in preeclamptic patients. However, in platelet poor plasmas obtained from normal platelet rich plasmas activated with thrombin (0.1 IU/ml, 37° C, 1 min), an increase of about 300 ng/ ml in β-thromboglobulin was observed while the increase in plasminogen activator inhibitor was only 4 ng/ml. It is concluded that the contribution of platelet plasminogen activator inhibitor-1 to the increase in plasma plasminogen activator inhibitor-1 levels in preeclamptic patients is negligible but the possibility that intravascular platelet activation indirectly contributes “in vivo” to the increase in plasma plasminogen activator inhibitor-1 levels in severe preeclampsia patients cannot be ruled out.